2020
DOI: 10.21061/jvs.v6i2.191
|View full text |Cite
|
Sign up to set email alerts
|

The State of Research in Veterans Studies: A Systematic Literature Review

Abstract: New areas of research on veterans are emerging as the field of veterans studies develops and grows. Yet gaps remain in interdisciplinary research efforts on veterans. The research available across disciplines is still too fragmented to coalesce into a full-fledged field of veteran studies, as other categorical, area, and identity fields of study have done so. By surveying research literature of multiple disciplines used in the curricula of higher education-level veteran study programs, this article presents a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Because of the long history of serving in silence and only being able to serve openly within the past decade, and for transgender people since January 2021, LGBTQ+ veterans' experiences are often missing or viewed with a limited scope in research. Usually, the research conducted is with LGBTQ individuals utilizing US Department of Veterans Affairs (VA) or Veterans Health Administration (VHA) services, focused on risk-factors and identify barriers to care (Lira & Chandrasekar, 2020), but this research excludes talking to veterans about their experiences of discrimination, and the impacts of the bans from service on their lives now, their views of their service, as well as a lack of focus on utilizing resiliency factors as suggested by Colpitts & Gahagan (2016).…”
Section: Gaps In Lgbtq+ Veteran Researchmentioning
confidence: 99%
“…Because of the long history of serving in silence and only being able to serve openly within the past decade, and for transgender people since January 2021, LGBTQ+ veterans' experiences are often missing or viewed with a limited scope in research. Usually, the research conducted is with LGBTQ individuals utilizing US Department of Veterans Affairs (VA) or Veterans Health Administration (VHA) services, focused on risk-factors and identify barriers to care (Lira & Chandrasekar, 2020), but this research excludes talking to veterans about their experiences of discrimination, and the impacts of the bans from service on their lives now, their views of their service, as well as a lack of focus on utilizing resiliency factors as suggested by Colpitts & Gahagan (2016).…”
Section: Gaps In Lgbtq+ Veteran Researchmentioning
confidence: 99%
“…Military organizational research, in general, appears sparse (Gonzalez & Simpson, 2021;Lira & Chandrasekar, 2020). However, some recent studies captured military organizational phenomena (Cunningham et al, 2020;DiRenzo et al, 2017;McAllister et al, 2015;Meyer et al, 2013;Prudential, 2012;Sørlie et al, 2020;Teclaw et al, 2016).…”
Section: Military and Veteran Organizational Researchmentioning
confidence: 99%
“…Lira and Chandrasekar (2020) found only three veteran studies aligning with the field of management studies, while research saturation occurs more frequently related to transition experiences from the military to an academic setting where veterans receive education. Work is needed to further the field of organizational research related to veteran's experiences of transition to civilian workplaces (Gonzalez & Simpson, 2021;Lira & Chandrasekar, 2020). A recent study found veterans experienced "feelings of demotion" upon leaving the military and entering a new organization which impacted their ability to maintain employment (Harrod et al, 2017, p. 261).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation